Multiple auxin-response regulators enable stability and variability in leaf development - Israeli, Alon; Capua, Yossi; Shwartz, Ido; Tal, Lior; Meir, Zohar; Levy, Matan; Bar, Maya; Efroni, Idan; Ori, Naomi (Current biology, 2019)
Auxin-signal transduction is mediated by the antagonistic activity of transcriptional activators and repressors. Both activators and repressors belong to gene families, but the biological importance of this complexity is not clear. Here, we addressed this question using tomato leaf development as a model by generating and analyzing mutants in multiple auxin-response components. In developing compound tomato leaves, auxin promotes leaflet formation and blade growth, and in the intercalary regions between leaflets, auxin response is inhibited by the Aux/IAA protein ENTIRE (E). e mutants form simple leaves due to ectopic blade growth in the intercalary domain. Using this unique loss-of-function phenotype and genome editing of auxin-response factor (ARF) genes, encoding auxin-response activators, we identified the contribution of specific ARFs to the e phenotype. Mutations in the related ARFs SlMP, SlARF19A, and SlARF19B, but not SlARF7, reduced the leaf blade and suppressed the e phenotype in a dosage-dependent manner that correlated with their relative expression, leading to a continuum of shapes. While single e and slmp mutants affected blade growth in an opposite manner, leaves of e slmp double mutants were similar to those of the wild type. However, the leaf shape of e slmp was more variable than that of the wild type, and it showed increased sensitivity to auxin. Our findings demonstrate that the existence of multiple auxin-response repressors and activators stabilizes the developmental output of auxin and that tuning their activity enables shape variability. The increased complexity of the auxin response therefore balances stability and flexibility in leaf patterning.
Gesehen am 23.01.2020